Efficiency of teaching patients with early-stage rheumatoid arthritis - Evgenia Vladislavovna Orlova; D. E. Karateev (Современная ревматология)
Education programs are an important part of the management of patients with rheumatoid arthritis (RA).Objective: to develop a unified model of an education program for RA patients and to evaluate its efficiency at the early stage of the disease.Material and methods. A group education program was worked out with the support of the All-Russian public organization of the disabled “The Russian rheumatology organization “Nadezhda” (Hope)” and encompassed 4 daily classes lasting 90 min. All information was presented by a multidisciplinary team of specialists (rheumatologists, a cardiologist, a psychologist, a physiotherapist, and a physical trainer). The study included 55 patients with early RA (89.1% of women aged 18 to 62 years; the duration of the disease was 2 to 22 months); of them 25 were taught using the education program (a study group); 30 received drug therapy only (a control group). Following 3 and 6 months, the number of tender and swollen joints, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and pain were determined applying a 100-ml VAS, DAS28, HAQ, and RAPID3. Adherence to non-drug treatments was assessed employing a special patient questionnaire.Results. Three and six months after being taught, two patient groups showed increases in adherence to joint protection methods by 13 and 10 times (p<0.01), regular physical training by 4 and 3.25 times (p<0.01), uses of orthoses for the wrist joint by 2 times and 75% (p<0.01) and knee orthoses by 33.3 and 50.0% (p<0.01), and orthopedic insoles by 71.4 and 57.1% (p<0.01), respectively. Following 6 months, there were statistically significant differences between the two groups in most parameters (p<0.05), except for ESR, CRP, and DAS28 (p>0.05). Further more, a good response to treatment was significantly more common in these periods, as shown by the EULAR response criteria (DAS28): 56.3% versus 40% in the control group (p<0.05).Conclusion. The education program decreases the intensity of pain syndrome and improves the functional status and quality of life of patients with early RA within 6 months. Patient education enhances adherence to non-drug treatments. The highest positive result was achieved just 3 months later; it slightly tailed off at 6 months. This necessitates re-education in succeeding 3–6 months.